The Study of Asbab al-Nuzul in Surah Al-Dhuha: A Critical Analysis of Narrations by Al-Wahidi and Jalaluddin Al-Suyuti - Yanti, Lutfiya Nurmayanti (At-Tuhfah : Jurnal Studi Keislaman, 2025)
The study of Asbab al-nuzul is one of the essential aspects in comprehensively understanding the meaning of Quranic verses. Neglecting this knowledge may lead to misinterpretations or misunderstandings of the values contained within the verses. This research aims to analyze the narrations of the Asbab al-nuzul of Surah Al-Dhuha as mentioned in Asbāb Al-Nuzūl by Al-Wahidi and Lubābun Nuqūl fī Asbābin Nuzūl by Al-Suyuti, in order to determine which narrations are accepted or rejected, thus leading to a correct understanding of the Asbab al-nuzul of Surah Al-Dhuha. This study employs a descriptive and comparative analytical method to examine the narrations presented in both books. The findings indicate that the narrations regarding the Asbab al-nuzul of surah Al-Dhuha found in these two works include not only authentic (ṣaḥīḥ) and acceptable narrations but also weak or unreliable ones that cannot be used as authoritative evidence (ḥujjah). By first analyzing the status of these narrations, a more comprehensive understanding can be achieved, allowing for the identification of which narrations are credible and which are not in the study of the Asbab al-nuzul of Surah Al-Dhuha.